If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 30 = 3y + 60 Reorder the terms: 30 + 2y = 3y + 60 Reorder the terms: 30 + 2y = 60 + 3y Solving 30 + 2y = 60 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 30 + 2y + -3y = 60 + 3y + -3y Combine like terms: 2y + -3y = -1y 30 + -1y = 60 + 3y + -3y Combine like terms: 3y + -3y = 0 30 + -1y = 60 + 0 30 + -1y = 60 Add '-30' to each side of the equation. 30 + -30 + -1y = 60 + -30 Combine like terms: 30 + -30 = 0 0 + -1y = 60 + -30 -1y = 60 + -30 Combine like terms: 60 + -30 = 30 -1y = 30 Divide each side by '-1'. y = -30 Simplifying y = -30
| y-(-3)=-2/3(x-1) | | 1/(x^2-5x+6)-1/(x^2-3x+2) | | R-18=-8 | | 8a+3-5a=7a | | 7-(4y-5)=4-5y | | 6y^3-2y^2-20y= | | -2x-75=72-9x | | 2x-3y(4x+24)=-2 | | 9-m/7=5 | | 0.5x-7=11 | | -98-3x=4x+112 | | c+3+5= | | 15x+5x^2=0 | | (3x-6)+(2x)+(x+10)+x=360 | | 5(3x+5)=-16+26 | | 10-2d=20 | | 5n^2+30n-200=0 | | 42x^3+82x^2+20x= | | -33-4x=x+37 | | 220=5x | | -5x-16=36-9x | | (5a^2x+3ax^2-5x)+(2a^2x-5ax^2+7x)=0 | | 9/5x=-18 | | (12y+12)+21y= | | 4x+2(x+22)=74 | | (5a^2x+3ax^2-5x)+(2a^2x+5ax^2+7x)=0 | | -0.5*-7=11 | | 5x-4(4/3)=-7 | | 29--10x=-18x+91 | | 24-6x=2x-40 | | X^2-25x/5x | | 3x-54=33+6x |